Excessive Cytosolic DNA Fragments as a Potential Trigger of Graves’ Disease: An Encrypted Message Sent by Animal Models - Luo, Yuqian; Yoshihara, Aya; Oda, Kenzaburo; Ishido, Yuko; Suzuki, Koichi (Frontiers in Endocrinology, 2016)
Graves’ hyperthyroidism is caused by autoantibodies directed against the thyroid stimulating hormone receptor (TSHR) that mimic the action of TSH. The establishment of Graves’ hyperthyroidism in experimental animals has proven to be an important approach to dissect the mechanisms of self-tolerance breakdown that lead to the production of thyroid-stimulating TSHR autoantibodies (TSAbs). ‘Shimojo’s model was the first successful Graves’ animal model, wherein immunization with fibroblasts cells expressing TSHR and a major histocompatibility complex (MHC) class II molecule, but not either alone, induced TSAb production in AKR/N (H-2k) mice. This model highlights the importance of coincident MHC class II expression on TSHR-expressing cells in the development of Graves’ hyperthyroidism. These data are also in agreement with the observation that Graves’ thyrocytes often aberrantly express MHC class II antigens via mechanisms that remain unclear. Our group demonstrated that cytosolic self-genomic DNA fragments derived from sterile injured cells can induce aberrant MHC class II expression and production of multiple inflammatory cytokines and chemokines in thyrocytes in vitro, suggesting that severe cell injury may initiate immune responses in a way that is relevant to thyroid autoimmunity mediated by cytosolic DNA signaling. Furthermore, more recent successful Graves’ animal models were primarily established by immunizing mice with TSHR-expressing plasmids or adenovirus. In these models, double-stranded DNA vaccine contents presumably exert similar immune-activating effect in cells at inoculation sites and thus might pave the way toward successful Graves’ animal models. This review focuses on evidence suggesting that cell injury-derived self-DNA fragments could act as Graves’ disease triggers.